2009
DOI: 10.1128/iai.00115-09
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Alpha-Hemolysin Monoclonal Antibodies Mediate Protection againstStaphylococcus aureusPneumonia

Abstract: Staphylococcus aureus pneumonia is one of the most common invasive diseases caused by this human pathogen. S. aureus alpha-hemolysin, a pore-forming cytotoxin, is an essential virulence factor in the pathogenesis of pneumonia. Vaccine-based targeting of this toxin provides protection against lethal staphylococcal pneumonia in a murine model system, suggesting that a monoclonal antibody-based therapy may likewise prove to be efficacious for prevention and treatment of this disease. We report the generation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
174
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(184 citation statements)
references
References 28 publications
6
174
1
Order By: Relevance
“…Frozen, homogenized skin and lung tissue samples were thawed and diluted to 1 mg/ml total protein in PBS plus a protease inhibitor (Roche). The concentration of Hla present in each sample was determined by plating 100 g of each sample onto a MaxiSorp microtiter plate (Thermo-Fisher Scientific) coated with 1 g/ml 7B8, a monoclonal antibody to Hla (35), and compared to a standard curve of purified Hla H35L , a recombinant inactive toxin variant that represents the monomeric form of Hla (36). The total amount of Hla (g) present per skin abscess or lung tissue was calculated by taking the concentration of Hla in the sample determined by an enzyme-linked immunosorbent assay (ELISA) and multiplying it by the dilution factor of the sample diluted at 1 mg/ml.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Frozen, homogenized skin and lung tissue samples were thawed and diluted to 1 mg/ml total protein in PBS plus a protease inhibitor (Roche). The concentration of Hla present in each sample was determined by plating 100 g of each sample onto a MaxiSorp microtiter plate (Thermo-Fisher Scientific) coated with 1 g/ml 7B8, a monoclonal antibody to Hla (35), and compared to a standard curve of purified Hla H35L , a recombinant inactive toxin variant that represents the monomeric form of Hla (36). The total amount of Hla (g) present per skin abscess or lung tissue was calculated by taking the concentration of Hla in the sample determined by an enzyme-linked immunosorbent assay (ELISA) and multiplying it by the dilution factor of the sample diluted at 1 mg/ml.…”
Section: Methodsmentioning
confidence: 99%
“…In order to determine the differential contributions of Hla and PSMs to epithelial cell injury, we examined the ability of S. aureus USA300 wild-type (WT), Hla Ϫ (⌬hla), and PSM Ϫ (⌬psm␣ psm␤ hld) strains to induce A549 alveolar epithelial cytotoxicity in an in vitro coculture assay. Previous studies using this assay system demonstrated an essential role for Hla in cellular injury, as loss of expression of Hla by S. aureus, antagonism of Hla by monoclonal antibodies or small-molecule inhibitors, or small interfering RNA (siRNA)-mediated knockdown of A549 ADAM10 expression markedly attenuated staphylococcal killing (14,22,35,39,40). The addition of early-exponentialphase WT S. aureus inocula across a range of staphylococcal culture dilutions directly correlated with the amount of A549 cell injury observed following a 3-h coculture (Fig.…”
Section: Psm Expression Regulates Hla Production In Vitromentioning
confidence: 99%
“…Twelve distinct alpha-toxin sequence types were identified from the 197 hla-positive isolates, and MEDI4893 neutralized alpha-toxin produced by all 12 different variants. Based on these observations, the correlation of higher anti-alpha-toxin antibody levels to better clinical outcomes in epidemiological studies (36,48,51) and the efficacy of alpha-toxin MAbs or vaccines in animal models (27,(32)(33)(34), we have initiated a phase 2 clinical trial with MEDI4893 to prevent ventilator-associated S. aureus pneumonia. Further studies are under way to verify these observations among S. aureus pneumonia patients.…”
Section: Figmentioning
confidence: 99%
“…In murine S. aureus skin and soft tissue infection models, both active immunization with a nontoxigenic alpha-toxin mutant and passive immunization with alpha-toxinspecific antiserum or IgG significantly improved survival and reduced disease severity (27,(32)(33)(34). Antibodies against alpha-toxin were both necessary and sufficient for protection against soft tissue infection and were inversely associated with bacterial counts (32) and had a protective role in keratitis (35).…”
mentioning
confidence: 99%
“…It is generally considered that α-hemolysin plays a central role in the pathogenesis of staphylococcal infections, especially in pulmonary infections caused by these bacteria (Bubeck Wardenburg et al, 2007;Burlak et al, 2007;Montgomery et al, 2008). Approximately one half of staphylococcal necrotizing pneumonia cases affecting previously healthy adults and children are caused by community-associated MRSA strains (Ragle and Bubeck Wardenburg, 2009). Besides direct lysis of the pulmonary cells, α-hemolysin also activates alveolar macrophages or monocytes, induces massive polymorphonuclear leukocyte influx into lung parenchyma with subsequent degranulation and destruction of microvascular endothelium and adjacent tissues, and induces platelet-neutrophil co-aggregation leading to the host response to toxin that contribute to the severity of lung destruction (Parimon et al, 2013).…”
mentioning
confidence: 99%